High thermal conductive carbon fiber composite material for spacecraft structure and preparation method thereof

CN116494607BActive Publication Date: 2026-10-20SHANGHAI INST OF SATELLITE EQUIP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310334431.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-30
Publication Date
2026-10-20
Estimated Expiration
2043-03-30

AI Technical Summary

Technical Problem

[0005]本发明的目的是针对复合材料面外导热性能不佳的问题,提供一种适用于航天器结构的高导热碳纤维复合材料及其制备方法,在碳纤维预浸料层与层之间设置复合导热片层,达到改善碳纤维复合材料面外导热性能的目的

Benefits of technology

[0048](1)制备的碳纤维复合材料具有优良的导热性能,面外热导率大于10W/(m·K),根据所选用的碳纤维种类,面内任意方向的热导率均大于100W/(m·K)。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116494607B_ABST
    Figure CN116494607B_ABST
Patent Text Reader

Abstract

The application relates to a high-thermal-conductivity carbon fiber composite material suitable for a spacecraft structure and a preparation method thereof, wherein a composite thermal conductive sheet layer is arranged between carbon fiber prepreg layers, the purpose of improving the out-of-plane thermal conductivity of the carbon fiber composite material is achieved, and the high-thermal-conductivity carbon fiber composite material is prepared by adopting a vacuum hot-pressing tank forming method. The carbon fiber prepreg is prepared by a filament winding method, the thermal conductive sheet layer structure is composed of a carbon nanotube film and a chopped porous carbon fiber support layer, the carbon nanotube sheet layer is prepared by a vacuum-assisted self-assembly method, and the chopped porous carbon fiber support layer is prepared by dispersing, filtering, drying and hot-pressing the chopped porous carbon fiber. The method solves the problem of low out-of-plane thermal conductivity of the carbon fiber composite material, the prepared carbon fiber composite material has an out-of-plane thermal conductivity greater than 10 W / (m*K), according to the type of the selected carbon fiber, the in-plane thermal conductivity in any direction is greater than 100 W / (m*K), and the interlaminar shear strength is greater than 40 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of composite materials, specifically relating to a high thermal conductivity carbon fiber composite material suitable for spacecraft structures and its preparation method, especially the requirement for high thermal conductivity in composite materials. Background Technology

[0002] Lightweight design is a perpetual pursuit for satellite structures. Currently, the weight of satellite structural platforms is designed to be controlled within 12%, thus satellite platform structures extensively utilize high-specific-modulus, high-specific-strength carbon fiber composites, such as T700 / epoxy composites and M55J / cyanate ester composites, accounting for over 80%. As satellites develop towards higher spatial resolution, higher temporal resolution, higher positioning accuracy, and higher timing accuracy, high-performance spaceborne antennas, optical cameras, and other payload instruments place higher demands on the thermal conductivity and stability of the platform structure. Taking a large platform as an example, the payload mounting plate envelope size reaches Φ3400mm, the maximum payload weight is 800kg, and the on-orbit deformation of the payload mounting surface is required to be less than 30μm to avoid adversely affecting the satellite's resolution and accuracy. Therefore, existing carbon fiber composites are insufficient to meet the requirements of future spacecraft structures for minimal on-orbit deformation, necessitating research into high thermal conductivity composite materials.

[0003] A well-designed structure for high thermal conductivity carbon fiber composites is crucial for overcoming interfacial thermal resistance limitations and achieving high thermal conductivity. The goal is to construct efficient and continuous heat conduction pathways within the matrix. Current research focuses on using multi-scale methods to construct ordered thermally conductive network structures in high thermal conductivity resin matrices. Essentially, this involves introducing micro / nano particles with high thermal conductivity into the resin matrix. Therefore, when designing high thermal conductivity polymer-based composites, balancing the relationship and properties between the polymer matrix and the micro / nano particles is particularly important, and also includes the interfacial interactions between the polymer matrix and nanoparticles, as well as the pre-construction of the microstructure.

[0004] This invention proposes a high thermal conductivity carbon fiber composite material suitable for spacecraft structures and its preparation process. By setting a composite thermally conductive layer between carbon fiber prepreg layers, the aim is to obtain a carbon fiber composite material with high structural mechanical properties and high thermal conductivity, especially to improve the out-of-plane thermal conductivity of the composite material. Summary of the Invention

[0005] The purpose of this invention is to address the problem of poor out-of-plane thermal conductivity of composite materials by providing a high thermal conductivity carbon fiber composite material suitable for spacecraft structures and its preparation method. A composite thermally conductive sheet layer is set between the carbon fiber prepreg layers to improve the out-of-plane thermal conductivity of the carbon fiber composite material.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] This invention provides a high thermal conductivity carbon fiber composite material suitable for spacecraft structures. The high thermal conductivity carbon fiber composite material includes a carbon fiber prepreg layer and a composite thermally conductive sheet layer disposed between the carbon fiber prepreg layer and the layer. The composite thermally conductive sheet layer includes a carbon nanotube membrane and short-cut hollow carbon fiber membranes composited on both sides.

[0008] Preferably, the composite thermal conductive sheet layer between the carbon fiber prepreg layers is 1-3 layers.

[0009] Preferably, the thickness of the carbon fiber prepreg layer is 0.10-0.20 mm.

[0010] Preferably, the length of the chopped hollow carbon fibers in the chopped hollow carbon fiber membrane is 5-30 mm. If the chopped hollow carbon fibers are too long, they will not enhance the interlaminar shear properties; if they are too short, they will not enhance the thermal conductivity.

[0011] Preferably, the carbon nanotube membrane is composed of a single or double layer of multi-walled carbon nanotubes with a thickness of 100-200 μm and a diameter of 20-30 nm.

[0012] Preferably, the method for preparing the carbon fiber prepreg layer includes the following steps:

[0013] A1. Place the carbon fiber yarn roll on the yarn rack of the winding machine, and pass the yarn through the traction roller, the impregnation tank, the tension control wheel, and the yarn nozzle in sequence, and then fix it on the roll covered with release paper.

[0014] A2. Prepare the resin solution and dilute it with acetone to a concentration of 0.960 ± 0.005 g / cm³. 3 Then pour it into the impregnation tank, start the winding equipment, and prepare the prepreg;

[0015] A3. Allow the prepared prepreg to air dry at room temperature for 48-72 hours to obtain carbon fiber prepreg.

[0016] Preferably, in step A1, the carbon fiber is one or more of high-modulus carbon fiber, high-strength carbon fiber, and pitch-based carbon fiber; in step A2, the resin is one or more of epoxy resin, cyanate ester, and bismaleimide resin.

[0017] Preferably, the method for preparing chopped hollow carbon fiber membranes includes the following steps:

[0018] T1. The short-cut hollow carbon fibers are ultrasonically treated and then filtered.

[0019] T2. Mix silane coupling agent, ethanol, and distilled water, add the filtered short-cut hollow carbon fibers, and perform surface treatment.

[0020] T3. Filter the surface-treated short-cut hollow carbon fiber, disperse it in deionized water, add surfactant, and stir.

[0021] T4. After drying the chopped hollow carbon fibers, hot-press them to obtain a chopped hollow carbon fiber membrane.

[0022] Preferably, in step T1, the ultrasonic treatment involves ultrasonic vibration in acetone for 20-30 minutes, repeated 2-3 times. Ultrasonic treatment can clean the short-cut carbon fibers and also disperse them, breaking down the clusters of short-cut carbon fibers.

[0023] Preferably, in step T2, the silane coupling agent includes one or more of KH-540, KH-550, KH-560, and KH-792. The mass ratio of the silane coupling agent, ethanol, and distilled water is 1-5:70-80:20-30, preferably 1:80:20. Ethanol and distilled water are miscible in any proportion, and ethanol can provide active functional groups (hydroxyl groups), which helps dissolve the silane coupling agent. The silane coupling agent is a surface-modified short-cut carbon fiber that gives its surface active groups, resulting in high bonding strength with resin during curing.

[0024] Preferably, in step T2, the surface treatment time is 30-40 minutes, during which a hydrolysis reaction occurs. Hydrolysis is a chemical reaction that can graft active functional groups onto the carbon fiber surface, achieving the purpose of carbon fiber surface modification. Surface-modified carbon fibers can improve the mechanical properties of composite materials. The surface of the chopped hollow carbon fibers after surface treatment has hydroxyl and carboxyl active functional groups, making them easier to disperse in water or solvents. Furthermore, during the curing process, they react with the resin matrix to form chemical bonds, increasing the interfacial bonding strength. The chopped hollow carbon fiber membrane also serves to support the carbon nanotube membrane, improving interlaminar shear strength.

[0025] Preferably, in step T3, the surfactant can be one or more of sodium hexadecylbenzenesulfonate, potassium monododecyl phosphate, and sodium lauryl sulfate. The concentration of the surfactant is 2-5 mg / ml. The surfactant acts as a dispersant, making the carbon fibers easier to disperse in the solution. Carbon fiber surfaces lacking silane coupling agent treatment are inert, resulting in weak interlayer properties in the composite material. A lack of surface activity makes it difficult to disperse short-cut carbon fibers, leading to uneven film density and affecting performance.

[0026] Preferably, in step T3, the stirring is mechanical stirring for 20-30 minutes and at a speed of 1000-2000 r / min.

[0027] Preferably, in step T4, the hot-pressing temperature is 40-50℃, the pressure is 1.5-2.0 MPa, and the time is 10-15 min. The pressure determines the final film thickness, which can be adjusted accordingly. Conversely, the film thickness affects the composite material's properties. Excessive temperature will deactivate the surfactant, so a low temperature is used. In step T4, the chopped hollow carbon fibers are filtered, washed, and then air-dried; the air-drying is carried out at 20-30℃ for 48-72 hours.

[0028] Preferably, the method for preparing carbon nanotube membranes includes the following steps:

[0029] (1) Carbon nanotubes were added to a mixed solution of silane coupling agent, ethanol and distilled water for surface treatment;

[0030] (2) The surface-treated carbon nanotubes were filtered, dispersed in deionized water, and ultrasonically treated to obtain a suspension.

[0031] (3) Vacuum filter the suspension and then let it air dry;

[0032] (4) The dried carbon nanotubes are hot-pressed to obtain a carbon nanotube film.

[0033] Preferably, in step (1), the silane coupling agent includes one or more of KH-540, KH-550, KH-560, and KH-792. The mass ratio of silane coupling agent, ethanol, and distilled water is 1-5:70-80:20-30. The surface-treated carbon nanotubes have hydroxyl and carboxyl active functional groups, making them easier to disperse in water or solvents. During the curing process, they react with the resin matrix to form chemical bonds, increasing the interfacial bonding strength. The carbon nanotube film can reduce interfacial thermal resistance and effectively improve the thermal conductivity of the composite material in the thickness direction. The surface treatment time is 30-40 minutes, during which a hydrolysis reaction occurs.

[0034] Preferably, in step (2), the amount of carbon nanotubes added is 0.5-1.5 mg / ml, more preferably 1 mg / ml. The ultrasonic treatment time is 10-20 min, using an ultrasonic cleaner for ultrasonic vibration.

[0035] Preferably, in step (3), the airing time is 24-48 hours; the airing is carried out at room temperature.

[0036] Preferably, in step (4), the temperature of the hot pressing treatment is 40-50℃, the pressure is 1.5-2.0MPa, and the hot pressing time is 10-15min.

[0037] This invention also provides a method for preparing a high thermal conductivity carbon fiber composite material, the method comprising the following steps:

[0038] S1. Lay the carbon fiber prepreg onto the mold;

[0039] S2. Place the chopped hollow carbon fiber membrane on the carbon fiber prepreg described in step S1;

[0040] S3. Place the carbon nanotube membrane on the short-cut hollow carbon fiber membrane described in step S2;

[0041] S4. Place the short-cut hollow carbon fiber membrane on the carbon nanotube membrane described in step S3.

[0042] S5. Lay the carbon fiber prepreg onto the short-cut hollow carbon fiber membrane described in step S4; the resulting composite thermal conductive sheet layer can be 1-3 layers.

[0043] S6. Repeat steps S1-S5 or S2-S5 until the required number of layers is reached.

[0044] S7. The material obtained in step S6 is vacuum sealed and heated and pressurized to obtain a high thermal conductivity composite material suitable for spacecraft structures.

[0045] Preferably, in step S7, the heating and pressurizing curing specifically involves: heating to 177-180℃ at a rate of 0.80-1.5℃ / min, and holding at that temperature for 2-4 hours; then applying pressure at 100-115℃, with a pressure of 0.1-0.6MPa and a vacuum level better than -0.097MPa. The preferred heating temperature is 177℃, which is the optimal temperature for achieving the desired degree of curing, derived from curing kinetics. Temperatures that are too high or too low will reduce the mechanical properties of the resin matrix. Applying pressure at 100-115℃ allows for control of the resin content in the composite material; aerospace composite materials typically have a resin content of 60% ± 3%. A heating rate that is too fast will prevent the effective release of internal stress within the material, leading to deformation of the molded material; a rate that is too slow will increase manufacturing costs.

[0046] The most significant improvement of this invention is the embedding of short-cut carbon fiber films between the composite materials, acting as a "skeleton." This enhances both thermal conductivity and interlaminar shear strength. In contrast, simply placing carbon nanotube films between the carbon fiber layers results in ineffective interlaminar bonding, low interlaminar shear strength, and poor thermal conductivity.

[0047] Compared with the prior art, the present invention has the following advantages:

[0048] (1) The prepared carbon fiber composite material has excellent thermal conductivity, with an out-of-plane thermal conductivity greater than 10 W / (m·K) and an in-plane thermal conductivity greater than 100 W / (m·K) in any direction depending on the type of carbon fiber used.

[0049] (2) By setting different thermal conductive layer structures (referring to the number of thermal conductive layers set between carbon fiber prepreg layers), flexible thermal conductivity can be obtained. The thermal conductive layers between carbon fiber prepregs can be multiple. Attached Figure Description

[0050] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings:

[0051] Figure 1 This is a schematic diagram of the preparation of carbon fiber prepreg in Example 1; wherein: 1-yarn roll, 2-traction roller, 3-impregnation tank, 4-tension control wheel, 5-yarn nozzle, 6-winding cylinder, 7-yarn release angle;

[0052] Figure 2 This is a schematic diagram of the high thermal conductivity carbon fiber composite material structure of the present invention; wherein: 8-carbon fiber prepreg layer; 9-short-cut hollow carbon fiber membrane; 10-carbon nanotube membrane. Detailed Implementation

[0053] The present invention will be described in detail below with reference to embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make several adjustments and improvements without departing from the concept of the present invention. These all fall within the protection scope of the present invention.

[0054] The high thermal conductivity carbon fiber composite material (single-layer composite thermally conductive sheet) prepared by this invention has the following structure: Figure 2 As shown, it includes a carbon fiber prepreg layer 8; a composite thermal conductive sheet layer disposed between the carbon fiber prepreg layer and the layer, the composite thermal conductive sheet layer including a carbon nanotube membrane 10 and short-cut hollow carbon fiber membranes 9 composite on both sides.

[0055] Example 1

[0056] High thermal conductivity domestically produced M55JB carbon fiber reinforced epoxy resin composite material

[0057] Step 1: Preparation of carbon fiber prepreg, equipment such as Figure 1 As shown, it includes a yarn roll 1, a traction roller 2, a sizing tank 3, a tension control wheel 4, a yarn nozzle 5, a winding drum 6, and a yarn release angle 7. The carbon fiber yarn roll is set with a yarn release angle and passes through the traction roller 2, the sizing tank 3, the tension control wheel 4, and the yarn nozzle 5 in sequence, and finally is wound onto the winding drum 6.

[0058] The preparation method is as follows:

[0059] 1) Place the domestic M55JB grade carbon fiber yarn roll on the yarn rack of the winding machine, and pass the yarn through the traction roller, the impregnation tank, the tension control wheel, and the yarn nozzle in sequence, and then fix it on the roll covered with release paper.

[0060] 2) Adjust the unwinding tension to 300-500g and the unwinding angle to 5-10°;

[0061] 3) Prepare epoxy resin AG80 adhesive solution, with the epoxy resin system formulated at a weight ratio of AG80:BF3C2H6:DDS = 100:30:1;

[0062] 4) Add acetone to the adhesive solution and measure the density using a densitometer (range 0.9-1.0 g / cm³). 3 Test the density of the adhesive solution and dilute it to 0.960±0.005 g / cm³. 3 Then pour it into the impregnation tank, start the winding equipment, and prepare the prepreg;

[0063] 5) Remove the prepared prepreg and let it air dry at room temperature for 48 hours.

[0064] Step 2: Preparation of a short-cut hollow carbon fiber membrane, the method is as follows:

[0065] 1) Sonicate the short-cut hollow carbon fibers in acetone for 20 minutes, repeating three times;

[0066] 2) Mix silane coupling agent KH-550: ethanol: distilled water in a ratio of 1:80:20 and hydrolyze for 30 minutes;

[0067] 3) Filter the surface-treated short-cut hollow carbon fibers, disperse them in deionized water (1 mg / ml), add sodium cetylbenzenesulfonate with a concentration of 2 mg / ml, and mechanically stir for 30 min at a speed of 2000 r / min.

[0068] 4) After filtration and washing, the mixture is then left to air dry at room temperature for 48 hours, and finally hot-pressed at 50℃ and 2.0MPa for 10 minutes to obtain a short-cut hollow carbon fiber membrane.

[0069] Step 3: Preparation of a carbon nanotube membrane, the method is as follows:

[0070] 1) Add carbon nanotubes to a mixed solution of silane coupling agent KH-550: ethanol: distilled water = 1:80:20 and hydrolyze for 30 min;

[0071] 2) Filter the surface-treated carbon nanotubes and disperse them in deionized water (1 mg / ml). Use an ultrasonic cleaner to vibrate the suspension for 10 min.

[0072] 3) Vacuum filter the mixed solution and then let it air dry at room temperature for 48 hours;

[0073] 4) The dried carbon nanotubes were hot-pressed at 50℃ and 2.0MPa for 10 minutes to obtain a carbon nanotube film.

[0074] Step 4: Preparation of a unidirectional plate made of high thermal conductivity carbon fiber composite material. The preparation method is as follows:

[0075] 1) Lay the carbon fiber prepreg of the specified length and width onto the mold;

[0076] 2) Place a short-cut hollow carbon fiber membrane of specified length and width on the carbon fiber prepreg described in step 1);

[0077] 3) Place a carbon nanotube membrane of a specified length and width on the short-cut hollow carbon fiber membrane described in step 2);

[0078] 4) Place a short-cut hollow carbon fiber membrane of specified length and width on the carbon nanotube membrane described in step 3);

[0079] 5) Lay the carbon fiber prepreg of specified length and width onto the chopped hollow carbon fiber membrane described in step 4); as follows: Figure 2 As shown, short-cut hollow carbon fiber membranes 9 are composited on both sides of the carbon nanotube membrane 10 and placed in the middle of the carbon fiber prepreg layer 8.

[0080] 6) Repeat steps 2) through 5) 10 times;

[0081] 7) The material obtained in step 6) is vacuum sealed and heated and pressurized to obtain a high thermal conductivity composite material suitable for spacecraft structures. The curing process is 100℃ / 0.1MPa / 30min) + (177℃ / 0.3MPa / 3h, with a vacuum degree better than -0.097MPa.

[0082] The high thermal conductivity domestically produced M55JB grade carbon fiber reinforced epoxy resin composite material prepared in this embodiment had its thermal conductivity determined according to GB / T22588-2008 "Measuring Thermal Diffusion Coefficient or Thermal Conductivity by Flash Method", and its interlaminar shear strength determined according to GB / T30969-2014 "Test Method for Shear Strength of Short Beams of Polymer-Based Composite Materials". The properties of the composite material are shown in Table 1.

[0083] Example 2

[0084] High thermal conductivity domestic M55JB grade carbon fiber reinforced epoxy resin composite material

[0085] Repeat steps one through three of Example 1.

[0086] Step 4: Preparation of a unidirectional plate made of high thermal conductivity carbon fiber composite material, the method is as follows:

[0087] 1) Lay the carbon fiber prepreg of the specified length and width onto the mold;

[0088] 2) Place a short-cut hollow carbon fiber membrane of specified length and width on the carbon fiber prepreg described in step 1);

[0089] 3) Place a carbon nanotube membrane of a specified length and width on the short-cut hollow carbon fiber membrane described in step 2);

[0090] 4) Place a short-cut hollow carbon fiber membrane of specified length and width on the carbon nanotube membrane described in step 3);

[0091] 5) Lay the carbon fiber prepreg of specified length and width onto the short-cut hollow carbon fiber membrane described in step 4);

[0092] 6) Lay the carbon fiber prepreg of the specified length and width onto the carbon fiber prepreg described in step 5);

[0093] 7) Repeat steps 2) through 6) 10 times;

[0094] 8) The material obtained in step 7) is vacuum sealed and heated and pressurized to obtain a high thermal conductivity composite material suitable for spacecraft structures. The curing process is 100℃ / 0.1MPa / 30min) + (177℃ / 0.3MPa / 3h, with a vacuum degree better than -0.097MPa.

[0095] The high thermal conductivity domestically produced M55JB grade carbon fiber reinforced epoxy resin composite material prepared in this embodiment had its thermal conductivity determined according to GB / T22588-2008 "Measuring Thermal Diffusion Coefficient or Thermal Conductivity by Flash Method", and its interlaminar shear strength determined according to GB / T30969-2014 "Test Method for Shear Strength of Short Beams of Polymer-Based Composite Materials". The properties of the composite material are shown in Table 1.

[0096] Example 3

[0097] High thermal conductivity domestic pitch-based carbon fiber reinforced cyanate composite material

[0098] Step 1: Preparation of domestically produced pitch-based carbon fiber prepreg, the method is as follows:

[0099] 1) Place the domestic pitch-based carbon fiber yarn roll on the yarn frame of the winding machine, and pass the yarn through the traction roller, the impregnation tank, the tension control wheel, and the yarn nozzle in sequence, and then fix it on the roll covered with release paper.

[0100] 2) Adjust the tension to 300-500g, and the unwinding angle to less than 5-10°;

[0101] 3) Dilute the cyanate ester prepolymer with acetone to 0.960±0.005 g / cm3 and pour it into the impregnation tank. Start the winding equipment to prepare the prepreg.

[0102] Then repeat steps two through four of Example 1.

[0103] The domestically produced pitch-based carbon fiber uses TC-HC-800 pitch-based carbon fiber from Shaanxi Tianze New Material Technology Co., Ltd.

[0104] The cyanate prepolymer used is the C01P0 series of bisphenol A cyanate prepolymer from Yangzhou Tianqi New Materials Co., Ltd.

[0105] The high thermal conductivity domestically produced asphalt-based reinforced cyanate ester composite material prepared in this embodiment had its thermal conductivity determined according to GB / T 22588-2008 "Determination of Thermal Diffusion Coefficient or Thermal Conductivity by Flash Method", and its interlaminar shear strength determined according to GB / T 30969-2014 "Test Method for Shear Strength of Short Beams of Polymer-Based Composite Materials". The properties of the composite material are shown in Table 1.

[0106] Example 4

[0107] High thermal conductivity domestic pitch-based carbon fiber reinforced cyanate ester composite material.

[0108] Repeat the first step in Example 3.

[0109] Step 2: Preparation of a short-cut hollow carbon fiber membrane, the method is as follows:

[0110] 1) Sonicate the short-cut hollow carbon fibers in acetone for 20 minutes, repeating three times;

[0111] 2) Filter the ultrasonically chopped hollow carbon fibers, disperse them in deionized water, add sodium cetylbenzenesulfonate at a concentration of 2 mg / ml, and mechanically stir for 30 min at a speed of 2000 r / min.

[0112] 3) After filtration and washing, the mixture is then left to air dry at room temperature for 48 hours, and finally hot-pressed at 50℃ and 2.0MPa for 10 minutes to obtain a short-cut hollow carbon fiber membrane.

[0113] Step 3: Preparation of a carbon nanotube membrane, the method is as follows:

[0114] 1) Sonicate the carbon nanotubes in acetone for 20 minutes, repeating three times;

[0115] 2) Vacuum filter the ultrasonicated carbon nanotubes, disperse them in deionized water, add sodium hexadecylbenzenesulfonate at a concentration of 2 mg / ml, and mechanically stir for 30 min at a speed of 2000 r / min. Then let it air dry at room temperature for 48 h;

[0116] 3) The dried carbon nanotubes were hot-pressed at 50℃ and 2.0MPa for 10 minutes to obtain a carbon nanotube film.

[0117] Repeat step four in Example 1.

[0118] The domestically produced pitch-based carbon fiber uses TC-HC-800 pitch-based carbon fiber from Shaanxi Tianze New Material Technology Co., Ltd.

[0119] The cyanate prepolymer used is the C01P0 series of bisphenol A cyanate prepolymer from Yangzhou Tianqi New Materials Co., Ltd.

[0120] The high thermal conductivity domestically produced asphalt-based reinforced cyanate ester composite material prepared in this embodiment had its thermal conductivity determined according to GB / T 22588-2008 "Determination of Thermal Diffusion Coefficient or Thermal Conductivity by Flash Method", and its interlaminar shear strength determined according to GB / T 30969-2014 "Test Method for Shear Strength of Short Beams of Polymer-Based Composite Materials". The properties of the composite material are shown in Table 1.

[0121] Example 5

[0122] High thermal conductivity domestic pitch-based carbon fiber reinforced cyanate composite material

[0123] Repeat the first step in Example 3.

[0124] Step 2: Preparation of a short-cut hollow carbon fiber membrane, the method is as follows:

[0125] 1) Sonicate the short-cut hollow carbon fibers in acetone for 20 minutes, repeating three times;

[0126] 2) Mix silane coupling agent KH-550: ethanol: distilled water in a ratio of 1:80:20 and hydrolyze for 30 minutes;

[0127] 3) After the surface-modified chopped hollow carbon fibers are filtered and washed with water, they are then dried at room temperature for 48 hours and finally hot-pressed at 50℃ and 2.0MPa for 10 minutes to obtain a chopped hollow carbon fiber membrane.

[0128] Step 3: Preparation of a carbon nanotube membrane, the method is as follows:

[0129] 1) Add carbon nanotubes to a mixed solution of silane coupling agent KH-550: ethanol: distilled water = 1:80:20 and hydrolyze for 30 min;

[0130] 2) Filter the surface-modified carbon nanotubes and then let them air dry at room temperature for 48 hours;

[0131] 3) The dried carbon nanotubes were hot-pressed at 50℃ and 2.0MPa for 10 minutes to obtain a carbon nanotube film.

[0132] Repeat step four in Example 1.

[0133] The domestically produced pitch-based carbon fiber uses TC-HC-800 pitch-based carbon fiber from Shaanxi Tianze New Material Technology Co., Ltd.

[0134] The cyanate prepolymer used is the C01P0 series of bisphenol A cyanate prepolymer from Yangzhou Tianqi New Materials Co., Ltd.

[0135] The high thermal conductivity domestically produced asphalt-based reinforced cyanate ester composite material prepared in this embodiment had its thermal conductivity determined according to GB / T 22588-2008 "Determination of Thermal Diffusion Coefficient or Thermal Conductivity by Flash Method", and its interlaminar shear strength determined according to GB / T 30969-2014 "Test Method for Shear Strength of Short Beams of Polymer-Based Composite Materials". The properties of the composite material are shown in Table 1.

[0136] Table 1 Properties of High Thermal Conductivity Composite Materials

[0137]

[0138] Note: Fiber content is homogenized to 60%.

[0139] As can be seen from Examples 1-3, the high thermal conductivity carbon fiber composite materials prepared using this invention exhibit in-plane thermal conductivity of 169-486 W / (m·K), surface thermal conductivity of 11-20 W / (m·K), and interlaminar shear strength of 46-64 MPa. Example 3 shows the highest in-plane thermal conductivity because the pitch-based carbon fiber itself has a thermal conductivity of 800 W / (m·K), significantly higher than the M55JB grade carbon fiber used in Examples 1 and 2. Example 2 exhibits higher interlaminar shear strength due to the inclusion of more thermally conductive layers, in which the chopped hollow carbon fiber membrane enhances interlaminar properties.

[0140] In Example 4, no surface modification treatment was performed on the chopped hollow carbon fibers and carbon nanotubes, resulting in low shear strength of the composite material. In Example 5, no surfactant was added during the dispersion process of the chopped hollow carbon fibers and carbon nanotubes, leading to uneven dispersion and inconsistent film thickness, which in turn reduced the interlaminar shear properties of the composite material. Films prepared from surface-treated chopped hollow carbon fibers and carbon nanotubes can effectively bond with the resin matrix, improving interlaminar properties. Surfactants can ensure uniform dispersion of micro / nano-sized chopped hollow carbon fibers and carbon nanotubes, resulting in films with uniform areal density and thickness, which plays a crucial role in improving the interlaminar shear strength of the composite material. The composite materials in Examples 4 and 5 were prepared using the same layup configuration, therefore their thermal conductivity properties are similar. The high thermal conductivity carbon fiber composite material prepared using this invention possesses both excellent thermal conductivity and mechanical properties, making it suitable for application in spacecraft structural / functional components.

[0141] Comparative Example 1

[0142] The carbon fiber reinforced epoxy resin composite material of this comparative example is prepared in a basically the same way as that in Example 1, except that: no short-cut hollow carbon fiber membrane was prepared, and the carbon fiber prepreg and carbon nanotube membrane were directly stacked together.

[0143] Carbon fiber reinforced epoxy resin composites with only carbon nanotube membranes will result in ineffective interlayer bonding and low interlayer shear strength.

[0144] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A high thermal conductivity carbon fiber composite material suitable for spacecraft structures, characterized in that, The high thermal conductivity carbon fiber composite material includes a carbon fiber prepreg layer and a composite thermally conductive sheet layer disposed between the carbon fiber prepreg layer; the composite thermally conductive sheet layer includes a carbon nanotube membrane and short-cut hollow carbon fiber membranes composited on both sides; The preparation method of chopped hollow carbon fiber membrane includes the following steps: T1. The short-cut hollow carbon fibers are ultrasonically treated and then filtered. T2. Mix silane coupling agent, ethanol, and distilled water, add the filtered short-cut hollow carbon fibers, and perform surface treatment. T3. Filter the surface-treated short-cut hollow carbon fiber, disperse it in deionized water, add surfactant, and stir. T4. After stirring, the chopped hollow carbon fibers are left to dry and then subjected to hot pressing to obtain a chopped hollow carbon fiber membrane.

2. The high thermal conductivity carbon fiber composite material according to claim 1, characterized in that, The length of the chopped hollow carbon fiber in the chopped hollow carbon fiber membrane is 5-30 mm; the carbon nanotube membrane is composed of single or double-layer multi-walled carbon nanotubes with a thickness of 100-200 μm and a diameter of 20-30 nm.

3. The high thermal conductivity carbon fiber composite material according to claim 1, characterized in that, In step T2, the silane coupling agent includes one or more of KH-540, KH-550, KH-560, and KH-792.

4. The high thermal conductivity carbon fiber composite material according to claim 1, characterized in that, In step T3, the surfactant includes one or more of sodium hexadecylbenzenesulfonate, potassium monododecyl phosphate, and sodium lauryl sulfate.

5. The high thermal conductivity carbon fiber composite material according to claim 1, characterized in that, In step T4, the hot pressing temperature is 40-50 ℃, the pressure is 1.5-2.0 MPa, and the time is 10-15 min.

6. The high thermal conductivity carbon fiber composite material according to claim 1, characterized in that, The preparation method of carbon nanotube membranes includes the following steps: (1) Carbon nanotubes were added to a mixed solution of silane coupling agent, ethanol and distilled water for surface treatment; (2) The surface-treated carbon nanotubes were filtered, dispersed in deionized water, and ultrasonically treated to obtain a suspension; (3) Vacuum filter the suspension and then let it air dry; (4) The dried carbon nanotubes are hot-pressed to obtain a carbon nanotube film.

7. The high thermal conductivity carbon fiber composite material according to claim 6, characterized in that, In step (4), the temperature of hot pressing is 40-50℃, the pressure is 1.5-2.0MPa, and the hot pressing time is 10-15min.

8. A method for preparing a high thermal conductivity carbon fiber composite material as described in claim 1, characterized in that, The preparation method includes the following steps: S1. Lay the carbon fiber prepreg onto the mold; S2. Place the chopped hollow carbon fiber membrane on the carbon fiber prepreg described in step S1; S3. Place the carbon nanotube membrane on the short-cut hollow carbon fiber membrane described in step S2; S4. Place the short-cut hollow carbon fiber membrane on the carbon nanotube membrane described in step S3. S5. Lay the carbon fiber prepreg onto the chopped hollow carbon fiber membrane described in step S4. S6. Repeat steps S1-S5 or S2-S5 until the required number of layers is reached. S7. The material obtained in step S6 is vacuum sealed and cured by heating and pressurizing to obtain a high thermal conductivity carbon fiber composite material suitable for spacecraft structures.

9. The high thermal conductivity carbon fiber composite material according to claim 8, characterized in that, In step S7, the heating and pressurizing curing specifically involves: heating temperature of 177-180 ℃, heating rate of 0.8~1.5 ℃ / min, and holding time of 2-4 h.

Citation Information

Patent Citations

  • Modified asphalt-based carbon fiber composite material for spacecraft load structure

    CN111319279A